A molecular switch in sulfur metabolism to reduce arsenic and enrich selenium in rice grain - Sun, Shengkai; Xu, Xuejie; Tang, Zhong; Tang, Zhu; Huang, Xin-Yuan; Wirtz, Markus; Hell, Rüdiger; Zhao, Fang-Jie (Nature Communications, 2021)
Rice grains typically contain high levels of toxic arsenic but low levels of the essential micronutrient selenium. Anthropogenic arsenic contamination of paddy soils exacerbates arsenic toxicity in rice crops resulting in substantial yield losses. Here, we report the identification of the gain-of-function arsenite tolerant 1 (astol1) mutant of rice that benefits from enhanced sulfur and selenium assimilation, arsenic tolerance, and decreased arsenic accumulation in grains. The astol1 mutation promotes the physical interaction of the chloroplast-localized O-acetylserine (thiol) lyase protein with its interaction partner serine-acetyltransferase in the cysteine synthase complex. Activation of the serine-acetyltransferase in this complex promotes the uptake of sulfate and selenium and enhances the production of cysteine, glutathione, and phytochelatins, resulting in increased tolerance and decreased translocation of arsenic to grains. Our findings uncover the pivotal sensing-function of the cysteine synthase complex in plastids for optimizing stress resilience and grain quality by regulating a fundamental macronutrient assimilation pathway.